2016
DOI: 10.3109/10717544.2016.1153745
|View full text |Cite
|
Sign up to set email alerts
|

A natural lipopeptide of surfactin for oral delivery of insulin

Abstract: Surfactin, a natural lipopeptide produced by Bacillus, is gaining attention for potentially biomedical and pharmaceutical applications. Here, surfactin was assayed for oral delivery of insulin (INS) by its ability to bind to and promote protein to penetrate through the cell membrane. Analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, surfactin was found to form co-precipitates with INS to protect it from acidic and enzymatic attack in the gastrointestinal tract. Further analysis by non-redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Balb/C mice (5–6 weeks old, 18–20 g body weight) were purchased from the center for disease prevention and control of Hubei province (Wuhan, China) following the University Ethics Committee’s guidelines. The mice were intraperitoneally injected with streptozotocin (70 mg/kg) for induction of T1DM (Zhang et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balb/C mice (5–6 weeks old, 18–20 g body weight) were purchased from the center for disease prevention and control of Hubei province (Wuhan, China) following the University Ethics Committee’s guidelines. The mice were intraperitoneally injected with streptozotocin (70 mg/kg) for induction of T1DM (Zhang et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we used the Bacillus -produced lipopeptide of surfactin (SFN) to improve INS uptake by the intestine and found the natural SFN and chemically synthesized analogs are all favorable for promoting INS uptake by the intestine (Zhang et al., 2016 , 2017 ). Addition to SFN, iturin (ITU) is another lipopeptide produced by Bacillus species with a well known anti-fungal activity (Zhao et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of insulin represents the most convenient route and attractive approach to developing systems that are capable of protecting insulin and enhancing its absorption [9]. Insulin is a peptide of almost negligible bioavailability (1%) when orally administered as a conventional solution, due to degradation by gastrointestinal protease enzymes, gastric acid inactivation and low intestinal membrane permeability [6]. Therefore, it has always been a challenge to establish oral formulation using different methods and technologies aiming to yield efficient and safe products.…”
Section: Oral Deliverymentioning
confidence: 99%
“…A bacillus lipopeptide product called surfactin promotes resistance to digestion by trypsin and pepsin with amphiphilic nature that gives it a strong biosurfactant action [6]. In vivo studies showed that the combination can produce a hypoglycaemic effect with relative bioavailability 12.48% for diabetic mice and 5.97% for non-diabetic dogs.…”
Section: Lipopeptidementioning
confidence: 99%
See 1 more Smart Citation